COST OF GOODS MANUFACTURING IMPLEMENTATION WITH JOB ORDER COSTING METHOD AT PT. CITRA SARUNG TANGAN INDONESIA - Fitriyani, Lita Yulita; Widyanti, Arum; Prasetio, Januar Eko (Journal of International Conference Proceedings, 2022)
ABSTRACTThis study aims to find empirical evidence related to the calculation of the cost of goods manufacturing to determine the selling price of PT. Citra Sarungtangan Indonesia, especially in orders for military gloves. Quantitative research is used, along with descriptive analysis that concentrates on the application of the calculation of the cost of goods ordered by PT. Citra Sarungtangan Indonesia. In this study describes PT. Citra Sarungtangan Indonesia sets the cost of ordered products on the basis of LOP (Labor, Overhead, and Profit) which is inaccurate because the calculation method does not group overhead costs according to the actual situation. The results showed that there were differences in the calculation of the cost of goods manufacturing between the LOP method and the Job Order Costing method. The results of calculations using the LOP method are known that the company recognizes profits that are too large compared to the Job Order Costing method. This can affect management decisions in the development and plans of the company in the future. PT. Citra Sarungtangan Indonesia should organize an order cost card, a working hour card, as well as in the charging of factory overhead costs, the cost of goods manufacturing is determined first.Keywords: Cost of Goods Manufacturing, Job Order Costing Method, LOP Method, PT. Citra Sarung Tangan Indonesia